Combined mild hydrocracking and fluid catalytic cracking process for efficient conversion of light cycle oil into high-quality gasoline. (15th May 2021) - Miao, Peipei; Zhu, Xiaolin; Guo, Yangling; Miao, Jie; Yu, Mengyun; Li, Chunyi
Graphical abstract: Highlights: High hydrogen transfer reactivity of hydrogenated LCO goes against gasoline yield. Mild hydrocracking contributes to the ring-opening reaction of naphtheno-aromatics. Unreacted LCO can be further cracked into high-quality gasoline by FCC process. The efficient production of high-quality gasoline is achieved in MHC-FCC process. Abstract: The hydrocracking process and the combined process of hydrogenation and catalytic cracking (HCC) are the common processes to convert inferior light cycle oil (LCO) into gasoline. In this work, the two processes were investigated and compared systematically. Based on the analysis of product distribution and hydrocarbon composition, it was found that, the higher hydrogen transfer reactivity of hydrogenated LCO in HCC process had an adverse effect on the yield of gasoline. While for the hydrocracking technology, the high conversion of LCO and high quality of gasoline were hardly satisfied simultaneously. In contrast, the mild hydrocracking process not only contributed to the ring-opening reaction of naphtheno-aromatics efficiently, but also yielded a higher content of aromatics in the gasoline product. The as-obtained unreacted light cycle oil (ULCO) from mild hydrocracking could be further treated in the fluid catalytic cracking unit, and the operating conditions for maximum high-quality gasoline production were optimized herein. Ultimately, a novel combined process of mild hydrocracking and catalytic cracking (MHC-FCC) was proposed. In the MHC-FCC process, LCO was primarily hydrocracked mildly, and then the ULCO was separated and subjected to catalytic cracking reaction, achieving a satisfying conversion ~85 wt% and high yield of high-quality gasoline ~65 wt%.